State authorization reciprocity agreement: participation and access to higher education. (4th May 2017) - Onwuameze, Nkechi
ABSTRACT: The State Authorization Reciprocity Agreement initiative was launched in 2014 to provide a uniform standard for the regulation of distance education across states in the United States. The system established by the National Council for State Authorization Reciprocity Agreement (NC-SARA) allows willing post-secondary institutions to participate voluntarily through a member state where their home campus is located. Since implementation, several states and institutions in the approved states have joined the interstate agreement. About 36 states and 613 institutions in the United States are participating in the interstate agreement as of January 2016. This study analyzed the pattern of participation among various institution types (public, private for-profit and private not-for-profit) and finds that participation amongst states and institutions has continued to increase since implementation of the interstate agreement. With the flexibility that distance learning offers, increased participation in SARA may translate into greater opportunities for participation in higher education.